Thymus satureoides Oil as Green Corrosion Inhibitor for 316L Stainless Steel in 3% NaCl: Experimental and Theoretical Studies - Simescu-Lazar, Florica; Slaoui, Soukaina; Essahli, Mohamed; Bohr, Frédéric; Lamiri, Abdeslam; Vanoye, Laurent; Chopart, Jean Paul (Lubricants, 2023)
The protection of 316L stainless steel in 3% NaCl by the essential oil of Thymus satureoides has been studied by many techniques such as potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), atomic force microscopy (AFM) and scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy analysis (EDXS). The results show that the corrosion rate of 316L stainless steel decreases with the increase in the concentration of the inhibitor up to an efficiency of 82% for a concentration of 1600 ppm. The Thymus satureoides oil acts as an anode inhibitor. The values of the inhibition effectiveness obtained from the polarization curves and electrochemical impedance spectroscopy (EIS) are in good agreement. Geometry optimization and calculation of the structural and electronic properties of the inhibitor molecular system have been carried out using density functional theory DFT (B3LYP, BMK and M062X) level with a 6-311++G** basis set.
Number: 2
Keywords: 3% NaCl solution; 316L stainless steel; DFT calculation; EIS; green corrosion inhibitor; polarization